Perancangan dan Pengembangan Company Profıle Berbasıs Web Pada Toko Byzen - Diny Anggriani Adnas; Jennifer Chandrinova (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Broadly speaking, company profile is a general description of a company that aims to provide a number of detailed information about the company's existence. Therefore, the company profile is considered to be able to increase customer awareness and attract attention. Toko Byzen is a business that sells a variety of kitchen utensils from the Tupperware brands that has been running for about 10 years. However, the media for conveying information about the shop is still in a traditional form such as print media and the information presented there is less detailed. Therefore, it is necessary to design a web-based company profile in order to improve the service of the store. The methodology applied in this research is waterfall method that aims to solve practical problems of the modern world. The final result of the research is in the form of a Web Company Profile that can be used as an asset or image of the store